Dampak investasi asing, inflasi, indeks pemberdayaan gender, dan indeks persepsi korupsi pada pertumbuhan ekonomi Indonesia - Hidayat, Dikky Nur; Yusuf, Ayus Ahmad (Journal of Economics Research and Policy Studies, 2024)
Gross domestic product is still the leading indicator in determining economic growth. As the economy in Indonesia grows, it is necessary to examine the factors driving gross domestic product. This study aims to analyze the effect of foreign investment, inflation, gender empowerment index, and corruption perception index on gross domestic product (GDP) in Indonesia in the period 2013-2022. The research method used is quantitative, with a panel data regression approach. The data used is secondary data obtained from various official sources, such as the Central Bureau of Statistics and Transparency International Indonesia. The dependent variable in this study is GDP, while the independent variables are foreign investment, inflation rate, gender empowerment index, and corruption perception index. The analysis results show that foreign investment and the gender empowerment index have a positive and significant effect on GDP, while inflation negatively affects GDP. Meanwhile, the corruption perception index does not affect Indonesia's GDP. These findings provide a deeper understanding of the factors affecting Indonesia's economic growth and the implications for future economic policy.